Blueshifted absorption lines from X-ray reflection in IRAS 13224−3809. Issue 2 (20th February 2020) - Fabian, A C; Reynolds, C S; Jiang, J; Pinto, C; Gallo, L C; Parker, M L; Lasenby, A N; Alston, W N; Buisson, D J K; Cackett, E M; De Marco, B; Garcia, J; et al.
ABSTRACT: We explore a disc origin for the highly blueshifted, variable absorption lines seen in the X-ray spectrum of the narrow-line Seyfert 1 galaxy IRAS 13224−3809. The blueshift corresponds to a velocity of ∼0.25 c . Such features in other active galactic nuclei are often interpreted as ultrafast outflows. The velocity is of course present in the orbital motions of the inner disc. The absorption lines in IRAS 13224−3809 are best seen when the flux is low and the reflection component of the disc is strong relative to the power-law continuum. The spectra are consistent with a model in which the reflection component passes through a thin, highly ionized absorbing layer at the surface of the inner disc, the blueshifted side of which dominates the flux due to relativistic aberration (the disc inclination is about 70°). No fast outflow need occurs beyond the disc.